THE CORRELATION BETWEEN SELF-CONFIDENCE AND SPEAKING SKILL OF THE PRE-INTERMEDIATE EFL STUDENTS - I Gusti Agung Ayu Risma Pradnya Suwari; Dewa Ayu Ari Wiryadi Joni; I Gusti Agung Putri Wirastuti (Journal on Studies in English Language Teaching (JOSELT), 2023)
Self-confidence has an important role in the learners’ willingness to communicate. The present study was to find out whether there was a significant correlation between self-confidence and speaking skill of the tenth-grade students of SMA N 1 Abiansemal in academic year 2022/2023. This research used an ex-post facto. The samples consisted of 34 students which were chosen by means of purposive cluster sampling method. The data were collected through administering the research instruments which were questionnaire and speaking test. The obtained data were statistically analyzed by using Pearson product moment correlation and t-test. The result of the data analysis clearly revealed that the alternative hypothesis was accepted. In other words, the research findings confirmed that there was a significant correlation between self-confidence and speaking skill of the tenth-grade students of SMA N 1 Abiansemal in academic year 2022/2023.